Polarized release of hepatic microRNAs into bile and serum in response to cellular injury and impaired liver function. (28th September 2015) - Verhoeven, Cornelia J.; Farid, Waqar R. R.; Roest, Henk P.; Ramakrishnaiah, Vedashree; de Ruiter, Petra E.; de Jonge, Jeroen; Kwekkeboom, Jaap; Metselaar, Herold J.; Tilanus, Hugo W.; Kazemier, Geert; Ijzermans, Jan N. M.; van der Laan, Luc J. W.
Abstract: Background & Aims: Extracellular microRNAs (miRNAs) in serum and bile are currently under intense investigation for biomarker purposes in liver disease. However, the directions and pathways by which miRNAs are released from hepatic cells remains largely unknown. Here, we investigated the release of hepatocyte and cholangiocyte‐derived miRNAs (HDmiRs and CDmiRs) into blood and bile during various (patho)physiological hepatic conditions. Methods: MiRNA release was analysed using longitudinally collected tissue and paired bile and serum samples ( n = 124) that were obtained from liver transplant recipients during follow‐up. Results: Cell‐type specificity of HDmiRs and CDmiRs was confirmed in liver and common bile duct biopsies ( P < 0.001). Analysis of paired bile and serum samples showed up to 20‐times higher miRNA‐levels in bile compared to serum ( P < 0.0001). Fractionation of bile showed the majority of miRNAs being present in the unpelletable supernatant, where protein conjunctions protect miRNAs against degradation ( P < 0.0001). During episodes of liver injury and histologically proven rejection in liver transplant recipients, relative HDmiR‐levels in bile decreased while its levels in serum increased ( P ≤ 0.015). Simultaneously, relative CDmiR‐levels in bile significantly increased, while their levels in serum decreased. Related to liver excretory function, a strong positive correlation was observed between HDmiR‐122 levels and bilirubin excretion into bile ( R = 0.694, P < 0.0001), whereas CDmiRs showed an inverse correlation ( P < 0.05). Conclusion: During impaired excretory function and injury, the liver shows polarized release of extracellular HDmiRs and CDmiRs. This sheds new light on the biology of hepatic miRNA release which is relevant for the interpretation of hepatic miRNAs as biomarkers.